2015
DOI: 10.1016/j.jconrel.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl pyrrolidone/bone morphogenetic protein-2 double delivery with in situ forming implants

Abstract: Bone morphogenetic proteins (BMPs) are growth and differentiation factors involved during development in morphogenesis, organogenesis and later mainly in regeneration processes, in particular in bone where they are responsible for osteoinduction. For more than a decade, recombinant human (rh)BMP-2 has been used in the clinic for lumbar spinal fusion at non-physiological high dosages that appear to be causative for side effects, like male sterility. A possible strategy to reduce the effective amount of rhBMP-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Using an in situ forming implants (ISFI) system; we developed a slow and sustained double delivery mechanism for rh BMP-2 and its enhancer NMP. Using the dual delivery ISFI system, rh BMP-2 and NMP were shown to bridge the critical size defect in the calvarial bone and aid in bone regeneration [51]. Thus enhancer small molecules like NMP could replace the high dose of BMPs and activate the action of the growth factors for efficient osteogenesis.…”
Section: Growth Factorsmentioning
confidence: 99%
“…Using an in situ forming implants (ISFI) system; we developed a slow and sustained double delivery mechanism for rh BMP-2 and its enhancer NMP. Using the dual delivery ISFI system, rh BMP-2 and NMP were shown to bridge the critical size defect in the calvarial bone and aid in bone regeneration [51]. Thus enhancer small molecules like NMP could replace the high dose of BMPs and activate the action of the growth factors for efficient osteogenesis.…”
Section: Growth Factorsmentioning
confidence: 99%
“…In calvarial defects of critical size in rabbits, it was demonstrated that the addition of NMP enhanced an ineffective rhBMP-2 dose (12  μ g), leading to significant bone regeneration compared to a control scaffold [10]. In the present study, a smaller dose (3.75  μ g) was applied to each sinus.…”
Section: Discussionmentioning
confidence: 78%
“…To date, few in vivo studies have tested the use of NMP for localized bone regeneration [11, 19], especially when using low-dose rhBMP-2 [10]. In calvarial defects of critical size in rabbits, it was demonstrated that the addition of NMP enhanced an ineffective rhBMP-2 dose (12  μ g), leading to significant bone regeneration compared to a control scaffold [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations